Pendampingan Umkm Berbasis Pembayaran Digital Dan Packaging Di Kelurahan Kp. Rambutan - Vionita, Deviyani; Utami, Novelia; Haryati, Eka; Hermansyah, Hermansyah (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This study discusses a mentorship program for MSMEs based on digital payment and product packaging in the Kp. Rambutan Village. The program aims to enhance the competitiveness and operational efficiency of MSMEs through the implementation of digital payment technology and the improvement of product packaging quality. The author's method involved conducting mentorship activities with business owners through interviews with MSME actors followed by explanations of the importance of digitization. The results showed that the application of digital payments via QRIS and the improvement of product packaging had a significantly positive impact on sales and customer satisfaction. Additionally, MSMEs in Kp. Rambutan reported increased efficiency and business management. These findings indicate that technology-based mentorship programs can be an effective strategy in supporting the development of MSMEs in the digital era.